Real World Posaconazole Pharmacokinetic Data in Paediatric Stem Cell Transplant Recipients - Csaba Kassa; Katalin Csordás; Lídia Hau; Orsolya Horváth; Krisztián Kállay; Gabriella Kertész; Márton Kiss; János Sinkó; Ágnes Wolfort; Gergely Kriván (Children)
Background: Invasive fungal disease is a significant cause of morbidity and mortality in allogeneic hematopoietic stem cell transplant (alloHSCT) recipients. Posaconazole, a broad-spectrum triazole, is widely used as prophylaxis. Methods: We conducted a monocentric, retrospective study to present real-world data on posaconazole trough levels in paediatric alloHSCT patients. The main objective was to determine the required daily dose of posaconazole in paediatric patients. We analysed factors influencing posaconazole levels, and the association between posaconazole levels and breakthrough fungal infection. Results: Among 102 allogeneic HSCT recipients, we measured posaconazole plasma concentrations in 548 blood samples. The required daily doses to reach a target range of 0.7–2.0 mg/L were 15.22 (suspension), 7.52 (tablet), and 7.84 mg/kg (intravenous). Patients aged < 13 years needed higher doses to achieve the target range. The presence of enteral symptoms during prophylaxis was associated with lower plasma concentrations (p < 0.001), while co-administration of proton pump inhibitors did not (p = 0.09). Eight breakthrough infections occurred; low levels of posaconazole (<0.7 mg/L) were observed in five out of eight cases. The Cox regression model showed that higher mean plasma concentrations decreased the hazard of breakthrough infections. Conclusions: The tablet and intravenous formulations of posaconazole outperformed the suspension in terms of predictability. Our analyses on breakthrough infections and posaconazole plasma levels suggest an exposure–response relationship.